Amplified spontaneous emission in CdS nanobelts: an investigation through ultrafast optical spectroscopy. - Sandy Adhitia Ekahana. (2011)
Cadmium sulfide nanomaterials hold promise in the application for various photonic devices such as gain medium for lasers indicated by the feature of amplified spontaneous emission (ASE). However, a complete description about the mechanism of this ASE process is yet to be available. This report attempts to give an integrated picture of the carrier dynamics of cadmium sulfide nanobelts until the population inversion for ASE is created. Initially the assignment of the defect states involved which plays a significant role in ASE are conducted by means of steady state and time resolved photoluminescence measurement. The interpretation is con rmed subsequently by a white light pump probe measurement. The result suggests that the population inversion is created at the free electron states supplied from the bound electron states where the surface related defects hinder the creation as it provides another fast transition channel.